GROWTH AND FORAGE YIELD OF TELANG FLOWER (Clitoria ternatea) GIVEN DIFFERENT FREQUENCY AND DOSE OF RABBIT MANURE FERTILIZER - A. F., Suprianto; Trisnadewi, A. A. A. S.; Wirawan, I W. (Jurnal Peternakan Tropika, 2024)
One One step to overcome the limitations of forage is to utilize the legume plant Clitoria ternatea. Inorganic fertilizers in the long run will damage the physical qualities of the soil which makes the soil hard and lumpy. Rabbit manure can be an alternative because it has high organic matter content, such as C/N ration (10-12%), P (2.20-2.76%), K (1.86%), Ca (2.08%), and pH (6.47-7.52) which are expected to increase the growth of Clitoria ternatea. The research lasted for 10 weeks (2 weeks of preparation, 8 weeks of data collection). The study used a complete 260 randomized design (CRD) factorial pattern with two factors. The first factor is the frequency of fertilizer application (F1 = 1 time) and (F2 = 2 times). The second factor was the fertilizer dose consisting of (D0 = 0 ton ha-1), (D5 = 5 ton ha-1), (D10 = 10 ton ha-1), (D15 = 15 ton ha-1), (D20 = 20 ton ha-1) so that there were 10 experimental units and each experimental unit was repeated 4 times so that 40 experimental pots were needed. The variables observed were growth, yield, and growth characteristics. The results showed an interaction between frequency and dose of rabbit manure fertilizer on the ratio of total forage dry weight to root dry weight. One time application and dosage 5 ton ha-1 of rabbit manure could give the best on growth and yield of Clitoria ternatea.